Wood anatomical and chemical properties related to the pulpability of Eucalyptus globulus: a review. Issue 1 (2nd January 2018) - Carrillo, Isabel; Vidal, Claudia; Elissetche, Juan P; Mendonça, Regis T
Abstract : Eucalyptus globulus is one of the most important hardwood species used by the pulp and paper industry due to its high pulp yield, high wood density, excellent fibre quality and good handsheet properties. However, the wood is a highly variable and complex material that has different chemical, physical and anatomical properties that influence its commercial value. Therefore, based on the wide variability between Eucalyptus trees and their economic importance, different studies have been focused on the amount, structure and behaviour of xylem components and their influence during pulping procedures. This review explores the most recent results on the chemical and anatomical variation in trees contrasting in wood density and pulp yield that explains the pulpability of E. globulus. In particular, the lignin chemistry, xylans features and fibre biometric properties of contrasting E. globulus trees are discussed in order to understand the remarkable performance of E. globulus during pulping procedures and paper manufacture. In addition, a genetic approach is made using the main results on the relationship between transcript abundance of genes associated with wood formation and the chemical properties of contrasting E. globulus genotypes.